2006
DOI: 10.1007/s11010-006-9264-x
|View full text |Cite
|
Sign up to set email alerts
|

Altered membrane free unsaturated fatty acid composition in human colorectal cancer tissue

Abstract: Polyunsaturated free fatty acids (PUFAs) participate in normal functioning of the cell, particularly in control intracellular cell signalling. As nutritional components they compose a human diet with an indirect promoting influence on tumourogenesis. The PUFAs level depends on the functional state of the membrane. This work is focused on changes only of free unsaturated fatty acids amount (AA - arachidonic acid, LA - linoleic acid, ALA - alpha-linolenic acid, palmitoleic acid (PA) and oleic acid) in cell membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…For these reasons, many researchers have focused their attention on possible associations between CRC progression and alterations in lipid levels. Swachowicz-Petelska et al observed that linoleic (LA) and α-linolenic (ALA) acid levels were lower in the cell membranes of colorectal cancer cells, whereas the levels of oleic (OA) and arachidonic acids were increased [12]. Moreover, these results were in accord with other observations of decreased levels of LA and ALA in the plasma of colorectal cancer patients [13,14].…”
Section: Introductionsupporting
confidence: 72%
“…For these reasons, many researchers have focused their attention on possible associations between CRC progression and alterations in lipid levels. Swachowicz-Petelska et al observed that linoleic (LA) and α-linolenic (ALA) acid levels were lower in the cell membranes of colorectal cancer cells, whereas the levels of oleic (OA) and arachidonic acids were increased [12]. Moreover, these results were in accord with other observations of decreased levels of LA and ALA in the plasma of colorectal cancer patients [13,14].…”
Section: Introductionsupporting
confidence: 72%
“…It is this potential that is the underlying characteristic of the cell that could distinguish between normal and cancerous cells. It was been noted before that cancerous cell have a lower membrane potential, and it has been shown that the cell's membrane changes during cancer transformation, in particular the membrane's fluidity and charge 41-42. Therefore, by altering the cell membrane potential, one could possibly control the fate of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, different biological conditions are associated with differences in membrane phospholipids composition particularly during cancer transformation (Dobrzyńska et al, 2005;Szachowicz-Petelska et al, 2007). For example, most cases of colorectal cancer involve an increase in the concentration of all phospholipid types at the cell membrane, including: phosphatidylinositol (PI), phosphatidylserine (PS), phosphatidylethanolamine (PE) and phosphatidylcholine (PC) ( Table 1).…”
Section: Changes In the Phospholipids Composition Of Human Colorectalmentioning
confidence: 99%